MOTIVASI LANSIA DALAM MENGIKUTI SENAM LANSIA PADA MASA PANDEMI COVID-19 DI DESA SERDANG, BARUSJAHE, KARO - Sindi Wahyunita Br Sitepu; Ramadi Ramadi; Rusmanto Rusmanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study was to determine the motivation of the elderly in participating in elderly gymnastics during the covid-19 pandemic in Serdang Village, Barusjahe, Karo. This research was conducted in Serdang Village, Barusjahe District, Karo Regency, North Sumatra, in September- March 2022 in Serdang Village. This research is a quantitative descriptive study using a survey method, the data collection technique is using a questionnaire. The population in this study were the elderly in Serdang Village, amounting to 35 people, which were taken using total sampling. Data analysis used descriptive analysis as stated in the form of percentages. The instrument validity test used the Pearson Product Moment formula with the results of 41 items valid for 45 statements. The reliability test uses the Alpha Cronbach formula of 0.919 so that the instrument is reliable. Based on the results of the study, it showed that the motivation of the elderly in participating in elderly gymnastics during the covid-19 pandemic in Serdang Village, Barusjahe, Karo was in the "high" category of 65.6%. Based on intrinsic factors are in the "high" category (69.5%) and extrinsic factors are in the "high" category (50.3%).Key Words: Motivation, Elderly Gymnastics, Pandemic covid-19